Теоретико - правові засади основних понять і термінів щодо раціонального використання та охорони грунтів. - Гавриш, Н.С.; Гавриш, Н.С.; Gavrish, N. (My University, 2012)
This article deals with the theoretic and law fundamentals of the notions and terms of rational use and protection of the soil. There is no identity deter- mined of the terms "ground" and "soil ", which are not similar and may not be identiﬁ ed. The notions "soil", "soil mass " and "soil mixture" are revealed and interpreted. "Soil" is a separate thing of ecological and legal relations and the mentioned notion has to be widely applied by the Environmental Law of Ukraine.
Гавриш, Н.С. Теоретико - правові засади основних понять і термінів щодо раціонального використання та охорони грунтів. / Н.С.Гавриш //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем,2012.–Вип.44.C. 57 - 66.
Keywords: Охорона грунтів; Поняття грунти; Раціональне використання грунтів; Єколого - правові відносини; Єкологічне право України; Экологическое право Украины; Эколого - правовые отношения; Рациональное использование грунтов; Понятие грунты; Охрана грунтов